Organotin Dithiocarbamates: Single-Source Precursors for Tin Sulfide Thin Films by Aerosol-Assisted Chemical Vapor Deposition (AACVD) - Ramasamy, K; Kuznetsov, V; Gopal, K; Malik, M; Raftery, J; Edwards, P; O'Brien, P (2013)
A series of diorganotin complexes of dithiocarbamates [Sn(C 4H9)2(S2CN(RR′) 2)2] (R, R′ = ethyl (1); R = methyl, R′ = butyl (2); R, R′ = butyl (3); R = methyl, R′ = hexyl (4); and [Sn(C6H5)2(S2CN(RR′) 2)2] (R, R′ = ethyl (5); R = methyl, R′ = butyl (6); R, R′ = butyl (7); R = methyl, R′ = hexyl (8) were synthesized. Single-crystal X-ray structures of 2, 3, and 8 were determined. Thermogravimetric analysis (TGA) showed single-step decomposition for the complexes 1, 3, and 5-8, and double-step decomposition for the complexes 2 and 4 between 195 C and 325 C. Complexes 1-4 were used as single-source precursors for the deposition of SnS thin films by aerosol-assisted chemical vapor deposition (AACVD) at temperatures from 400 C to 530 C. Orthorhombic SnS thin films were deposited from all four complexes at all deposition temperatures. The films were characterized by UV-vis spectroscopy, powder X-ray diffraction (p-XRD), Raman spectroscopy, scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and also electrical resistivity measurements. © Published 2013 by the American Chemical Society.